Development and validation of technologies suitable for the decontamination and re-use of contaminated N95 filtering facepiece respirators in response to the COVID-19 pandemic. (January 2022) - Alt, J.; Eveland, R.; Fiorello, A.; Haas, B.; Meszaros, J.; McEvoy, B.; Ridenour, C.; Shaffer, D.; Yirava, W.; Ward, L.
Summary: Background: Coronavirus disease 2019 (COVID-19) has brought significant challenges to society globally, particularly in the area of healthcare provision. A pressing need existed in protecting those tasked with delivering healthcare solutions during the COVID-19 crisis by providing solutions for preserving adequate supplies of effective personal protective equipment (PPE). Aim: To evaluate and validate available methods for the decontamination of N95 filtering facepiece respirators (FFRs) while maintaining functionality during re-use. Methods: Multiple low-temperature steam and vaporized hydrogen peroxide (VHP) technologies were assessed for inactivation of Mycobacterium spp. and feline calicivirus (employed as representatives of the contamination challenge). Findings: Virus (≥3log10 ) and Mycobacterium spp. (≥6log10 ) inactivation was achieved on various types of N95 FFRs using an array of heat (65–71 o C), humidity (>50% relative humidity) and VHP without affecting the performance of the PPE. Conclusion: The methods have been validated and were authorized by the US Food and Drug Administration under a temporary emergency use authorization. Based on the findings, opportunities exist for development and deployment of decontamination methods made from simple, general purpose materials and equipment should a future need arise.